Lewis and BrØnsted acid-catalyzed reactions of alcohol pro-electrophiles as novel synthetic strategies for C-X (X = C, N, O, S) bond formation - Zhang, Xiaoxiang (2011)
The work in this thesis was undertaken at the Division of Chemistry and Biological Chemistry, School of Physical and Mathematical Sciences, Nanyang Technological University from August 2007 to June 2011 under the supervision of Asst. Prof. Philip Wai Hong Chan. The work of this thesis has been directed toward establishing new Lewis and Brønsted acid-catalyzed reactions of alcohol pro-electrophiles as novel synthetic strategies for C-X (X = C, N, O, S) bond formation. This thesis is divided into three parts: Part I consists of Chapter I, which gives an introduction of Lewis and Brønsted acid catalyzed reactions of alcohol pro-electrophiles, particularly those containing a pendant activated alcohols such as allylic, propargylic, benzylic and cyclopropylmethyl functional group. Part II describes the new strategies developed for C-X (X = C, N, O, S) bond formation employing alcohols as pro-electrophiles. Chapter II reports iron(III) chloride catalyzed direct nucleophilic a-substitution of Morita-Baylis-Hillman alcohols with alcohols, arenes, 1,3-dicarbonyl compounds, and thiols. In Chapter III, a new method to indenols that relied on ytterbium(III) triflate catalyzed tandem Friedel-Crafts arylation/hydroarylation of propargylic alcohols with phenols is described. Chapter IV detailed the synthesis of highly substituted indene derivatives via Brønsted acid catalyzed intramolecular Friedel-Crafts cyclization of homoallylic alcohols. In Chapter V, a novel strategy to di- and trisubstituted thiazoles via Brønsted acid catalyzed cyclization of propargylic alcohols with thioamides was described. Chapter VI disclosed an efficient method for the preparation of di- and trisubstituted 2-aryloxazoles via ytterbium(III) triflate catalyzed cyclization of tertiary propargylic alcohols with aryl amides. Part III contains the experimental section (Chapter VII) and references section (Chapter VIII) pertaining to this thesis.